Social science on a world scale - Connell, Raewyn (Southernising criminology, 2024)
Parallel projects of class analysis, emerging at different points of the global periphery at similar times, pose the problem of connection around the periphery. This chapter gives an outline of the global economy of knowledge, centred on the Global North, which in this economy is the privileged site of theory (including methodology). The author discusses critiques and alternatives, particularly indigenous knowledge, decolonial perspectives, and Southern theory. She raises questions about the intellectual workforce, the labour process of knowledge formation, and the circulation of knowledge. Finally, she raises the possibility of a democratic world knowledge economy, based on an epistemology of solidarity. This chapter contributes to weaving a denser background for changing criminology, as part of the more general field of social science.